COVID-19 in benign hematology: emerging challenges and special considerations for healthcare professionals. Issue 10 (2nd October 2020) - Noun, Peter; Ibrahim, Ahmad; Hodroj, Mohammad Hassan; Bou-Fakhredin, Rayan; Taher, Ali T.
ABSTRACT: Introduction: Many patients with inherited or acquired benign hematological disorders are at increased risk of developing severe complications from COVID-19. These patients, therefore, require specific advice regarding isolation and changes to their usual treatment schedules. Their disease can also be associated with significant burden, and they necessitate life-long and regular access to therapy, and regular follow-up consultations and hospital visits. The current COVID-19 pandemic is therefore presenting many challenges for these patients, their families, and health-care professionals. Areas covered: This review provides an overview of the reported COVID-19 cases in the literature in patients with certain benign hematological disorders including thalassemia, sickle cell disease, hemophilia, immune thrombocytopenia, venous thromboembolism, and aplastic anemia. The review also outlines some recommendations on how to manage these patients if they are infected with SARS-CoV-2. To review the literature on benign hematological disorders and COVID-19, a bibliographic search was performed using PubMed for articles published between January 2020 and June 2020. Expert opinion: International efforts must be made to continue reporting and better understanding the effects of SARS-CoV-2 infection in these patients and accordingly develop a set of recommendations to optimize the treatment of future infected patients.